Treatment of Refractory No-Reflow in Cardiac Catheterization Laboratory; Role of Intracoronary Verapamil (A Case Report) - Kiani, Sadaf Shabbir; Nadeem, Asif; Chauhdry, Azhar Ali; Farahe, Ali; Shafique, Hafiz M; Ashraf, Waheed; Ismail, Muhammad; Saeed, Bilal; Zafar, Asma; Yousaf, Amna (Pakistan Armed Forces Medical Journal, 2022)
The no reflow phenomenon is a feared complication in Percutaneous Coronary Intervention (PCI) procedures including elective as well as primary PCI (Percutaneous Coronary Intervention), and results in worse prognosis. A number of etiological factors are involved in pathogenesis of no reflow phenomenon. These include distal athero embolization, ischemic and reperfusion injury, microvascular spasm and endothelial dysfunction. The treatment of no reflow depends on underlying mechanism and includes pharmacological as well as non-pharmacological interventions. Pharmacological agents include vasodilators like adenosine, sodium nitroprusside, verapamil, in addition to adrenaline (intracoronary) and, GpIIa/IIIb inhibitors. Non pharmacological measures include mechanical thrombus aspiration. Among pharmacological agents, Verapamil is usually the least preferred agent because of its negative ionotropic effect. Here, we describe a case of refractory no reflow in a patient undergoing primary PCI to right coronary artery (RCA), which was treated with a no. of pharmacological agents as well as aspiration thrombectomy but without much success and finally responded to intracoronary verapamil.